A history of British elections since 1689 - Cook, Chris, 1945-, author.
1 online resource (x, 458 pages)
Keywords: "Combines data tables, summary and analysis with thematic overviews and chronological outlines to provide a guide to British elections and electoral systems from 1689 to 2013"--